Fármacos utilizados empíricamente y su relación con las complicaciones respiratorias en adultos mayores de 65- 90 años, Rcto. María Obdulia, Ricaurte, Los Ríos, octubre 2019 - marzo del 2020. - Cabrera Reyes, Rosa Margarita (2020)
Introduction: The use of empirical drugs in older adults and the complications that develop in upper respiratory infections are a health problem, due to many factors that influence the onset and affect the respiratory system produced by viruses or bacteria. General objective: To determine whether the empirical use of drugs is related to respiratory complications in adults over 65- 90 years of age, Rcto. María Obdulia, Ricaurte, Los Ríos, October 2019 - March 2020. Methodology: It was qualitative-quantitative; because it helped to understand the scope and understanding of the problem, type was descriptive cross-sectional to understand why there is an indiscriminate use of drugs in older adults. Results: The study population has a period of age between 71 and 75 years (35%), with a higher prevalence among males (59%) of rural origin, the level of study is low at 71%, a large percentage use drugs empirically usually when they feel sick from respiratory infections, cough and flu with 39%, 88% prefer self-medication for not going to the doctor, 53% do not know of the adverse reactions from self-medication 52% buy medicines weekly without having been prescribed by the doctor. Conclusions: The use of empirical drugs is due to economic problems, due to mobility, lack of time and shifts in health centers this affects respiratory complications of the elderly.